Continuous high-altitude measurements of cosmic ray neutrons and SEU/MCU at various locations: correlation and analyses based-on MUSCA SEP³ - Hubert, G.; Velazco, R.; Federico, C.; Cheminet, A.; Silva Cardenas, C.; Caldas, L. V. E.; Pancher, F.; Lacoste, V.; Palumbo, Félix Roberto Mario; Mansour, W.; Artola, L.; Pineda, F.; et al. (Institute of Electrical and Electronics Engineers, 2013)
Fil: Hubert, G.. French Aerospace Lab, ONERA; Francia